2009
DOI: 10.1186/1743-8977-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of 24 manufactured nanoparticles in human alveolar epithelial and macrophage cell lines

Abstract: Background: A critical issue with nanomaterials is the clear understanding of their potential toxicity. We evaluated the toxic effect of 24 nanoparticles of similar equivalent spherical diameter and various elemental compositions on 2 human pulmonary cell lines: A549 and THP-1. A secondary aim was to elaborate a generic experimental set-up that would allow the rapid screening of cytotoxic effect of nanoparticles. We therefore compared 2 cytotoxicity assays (MTT and Neutral Red) and analyzed 2 time points (3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
267
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(293 citation statements)
references
References 28 publications
21
267
4
1
Order By: Relevance
“…However, its toxicity reduces in AuNPs treated with CMCS. In this study, Au + decreased mitochondrial activity more than AuNPs with almost two fold difference in IC 50 values as shown in Table 2, which agreed with previous studies of many researcher [25][26][27][28] MTT assay used to measure the cell viability expressed in the decrease in mitochondrial activity (Table3). A reduction in mitochondrial function of A549 cells exposed to the three GNPs types prepared.…”
Section: Figure 4:-sem and Edx Spectra Cotton Treated With Aunpssupporting
confidence: 91%
“…However, its toxicity reduces in AuNPs treated with CMCS. In this study, Au + decreased mitochondrial activity more than AuNPs with almost two fold difference in IC 50 values as shown in Table 2, which agreed with previous studies of many researcher [25][26][27][28] MTT assay used to measure the cell viability expressed in the decrease in mitochondrial activity (Table3). A reduction in mitochondrial function of A549 cells exposed to the three GNPs types prepared.…”
Section: Figure 4:-sem and Edx Spectra Cotton Treated With Aunpssupporting
confidence: 91%
“…7 Furthermore, among 24 manufactured nanoparticles, which were compared for their toxicity in vitro in human alveolar epithelial and macrophage cell lines, copper-and zinc-based nanoparticles appeared to be the most toxic, especially for human macrophages. 26 In this connection, the particle size seems to have an important role, for human epithelial cells, it was shown that nanoparticles of CuO were much more toxic compared with micrometer particles of CuO. 27 Although the median for the SAA increases after inhalation of zinc-containing welding fume is lower than the respective median after inhalation of "copper only" welding fume, the elevations of SAA are relatively high in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…With frequent exposure to dispersed nanoparticles from the composite products or workplaces, there is an increased chance for nanoparticles or nano composites to enter human body and to relocate in metabolism-active organs (Song et al 2009). Thus, studying the toxicity of nanomaterials is of importance to provide the guidance to occupational health and safety (Li et al 2008;Lanone et al 2009;Turkez et al 2013a). The discussion about safety concerns associated with small particles is ongoing for many decades and, to a large extent, is related to the potential risks following inhalative, oral, parenteral or dermal exposure ).…”
Section: Introductionmentioning
confidence: 99%